Does the development and implementation of a procedure-specific proforma for skin lesion surgery improve quality of operation notes?. (June 2021) - Masterton, Gary; Hassan, Deniz; Siddiqui, Aftab
Abstract: Background: Operation notes often have omissions and are difficult to locate in patients notes despite clear guidance from the Royal College of Surgeons (RCS) 'Good Surgical Practice' 2014 outlining what should be included in operation notes. Procedure-specific proformas are rarely used by Plastic surgeons despite being utilised by other specialities. With an alarming rise of incidence of skin malignancies there has been an increase in the number of skin lesions referred to Plastic surgeons for excision. The need for reliable, reproducible, accurate and easily accessible operating notes for skin lesion excision is pivotal for continuity of care and treatment planning. This study aimed at comparing the quality of skin lesion operation notes prior-to and after implementation of a procedure-specific proforma in relation to RCS recommendations. Methods: Fourteen parameters from the recommendations by the RCS 'Good Surgical Practice' 2014 guidelines were used to audit skin lesion operation notes. The study consisted of a retrospective audit of 80 operation notes and a prospective audit of 80 operation notes following the development and implementation of a skin lesion procedure-specific proforma. We assessed and compared the operation notes overall compliance with the RCS guidelines. Statistical analysis highlighting the difference between both groups was performed using the independent sample t -test. Results: After implementation of the skin lesion procedure-specific proforma, the average compliance with the RCS recommendations increased significantly from 87.5% retrospectively to 98.8% prospectively ( p -value 0.0414). In 6 of the 14 parameters assessed significant improvements with regards compliance to the guidelines was demonstrated. Conclusion: The development and implementation of a skin lesion procedure-specific proforma has demonstrated a significant improvement in the quality of operation notes within a Plastic surgery department which has the potential to minimise omissions and improve continuity of surgical patient care.